Organizational communication in building maintenance management - Yahya, Mohamad Ridzuan; Abdul Rahim, Asiah (IIUM Press, 2017)
Practicing building maintenance management in the high-rise commercial buildings are made up of complex communication activities involving many parties. It has therefore become an ineffective communication system among building maintenance stakeholders for supporting value aspect in the building particularly on the operation and maintenance activities. The testified statistical analysis indicates that, only eight (8) factors such as schedule for communication and information distribution, social and informal mechanisms for a cooperative working environment, arrangement of building maintenance management structure, building maintenance information with high quality content, building maintenance stakeholders’ experiences, capable building manager, building maintenance information documentation, and building maintenance communication media infrastructure discovered their impacts on the building maintenance communication performance which had a significant relationship with building maintenance communication effectiveness (BMCE). So, it can help maintenance management team to develop strategies for improving communication effectiveness during the operation and maintenance activities by applying needed actions to the related predicting communication performance indicators. In conclusion, effectively managing communication factors through communication performance indicators in building maintenance practice can improve the building maintenance management performance and further benefit for all building maintenance stakeholders and the objectives of the whole operation and building maintenance activities.